Fungsi Associated with Ipil-Ipil (Leucaena Leucocephala) (Lam) De with Seeds and Their Control - SEBASTIAN S QUINIONES (ASEAN Journal on Science and Technology for Development, 1986)
Thirteen fungi were isolated from Leucaena seeds from different places in the philipines. These were; Fusarium moniliforme, F. solani, F. semitecctum, Botryodiplodia theobromae, Cephalosporium sp., Phoma sp., Phoma sp., Cladosporiumsp., Chaetomium sp., Chaetomiun sp., Penicilium sp. and Aspergilus flavus. C. graminiculo completely inhibits the germination of seeds once it has colonized the seeds.